Laserpuncture Treatment for Cat Fractures at Airlangga University Veterinary Teaching Hospital - Sofyan, Miyayu Soneta; Yudaniayanti, Ira Sari (IPB University, 2025)
Cats are pets that are often found and commonly kept in Indonesia. Cats themselves are among the pets where many cases of bone fractures are found, which is one of the musculoskeletal disorders. Reports of these fracture cases are reviewed from a domestic female cat named Titi, with three colors of fur: orange, black, and white, aged 4 months, weighing 1.2 kg, and showing pain in her back and extremities when handled. The method of treatment in this case is to perform an X-ray to confirm the cat’s diagnosis. Then, laser puncture treatment is given as an alternative treatment provided for medical care due to the low costs required for the cat. Post-treatment care for the cat includes administering supportive medication such as multivitamins and minerals.